Subversion and the Storyteller: Exploring Spirituality and the Evolution of Traditional Narratives in Contemporary Native Literature in Canada - Shultis, Elizabeth E. (2011)
This thesis explores the intersection of storytelling and spirituality in contemporary Native literature in Canada. The invocation of the oral tradition and its history will be examined in the works of Eden Robinson, Joseph Boyden, and Harry Robinson, as each author attempts to orient his or her narratives within a First Nations framework. By gesturing towards orality in their written literature, these authors acknowledge the dialogic nature of a narrative that has been shaped by ancestral experiences and memory and thus write against the colonial master narrative of the contemporary Canadian nation-state. In Joseph Boyden's Through Black Spruce , Eden Robinson's Monkey Beach , and the transcribed collections of Harry Robinson's stories, the invocation of orality becomes the vehicle through which to explore Indigenous ways of knowing and traditional spiritual beliefs. This thesis first considers the ways in which the mode of storytelling allows each author to create a new narrative that introduces readers to an Indigenous perspective on the processes of history. It then examines the evolution of specific spiritual beings from traditional narratives into contemporary settings as a way to explore neocolonial attitudes and the compromised contexts of modern Indigenous life in communities across Canada that continue to be haunted by a legacy of colonialism. I end with an exploration of the potential for healing that each author envisions as communities move into a decolonization process through the regeneration of tribal languages, a reconnection to sacred space, and a reimagining of the Canadian master narrative and its colonial interpretation of history. Master of English